Towards user-orientated weather warnings. (September 2018) - Kox, Thomas; Kempf, Harald; Lüder, Catharina; Hagedorn, Renate; Gerhold, Lars
Abstract: National meteorological services are continually working on improvements of their weather and warning information. Based on five workshops with members of the German national meteorological service and with forecast end-users from emergency management, water management, road maintenance, the media, and others, we discuss operational practices regarding the processing of weather information and specific end-user needs. We focus on the question what users' requirements for a warning are and how meteorological services can address the various user needs. Results show that in order to improve weather (warning) communication, spatial and temporal precision, acceptability and comprehensibility as well as identification of relevant information and technical requirements need to be addressed. A new challenge is the inclusion of impact information provided by e.g. emergency services and social media. As we identify opportunities and constraints for future developments, we emphasise the importance of a strong cooperation and a constant dialogue and discussion of needs between meteorological services and end-users to ensure quality of impact-based forecasts.